The use of platelet-rich fibrin in orofacial aesthetic procedures: an integrative review - Lins, Vânia Feitosa (2021)
Platelet concentrates have been used for therapeutic purposes in humans for more than 60 years, showing promising results, since these platelets are obtained from the patient's autogenous blood. The PRF is part of the second generation of these concentrates, obtainable simplified and without the addition of biochemical products. Currently, these concentrates have become increasingly specific, which has favored their use in several areas, among them has been investigated as a tool for aesthetic procedures in the orofacial region. The objective of this work was to carry out an integrative literature review and analyze studies on the use of PRF as an adjunct in orofacial harmonization, its methodologies and results, in order to assess the effectiveness of the technique. The articles compiled in this study were selected through the databases: PubMed, Medline and Scielo. The survey was limited to articles published in the English and Portuguese languages, between the years 2010 to 2020. Although there are few specific studies involving these two areas of concentration, the results show that injectable PRF has been shown to be effective when used in procedures orofacial esthetics, responding effectively to tissue regeneration. Thus, the use of this technique can bring beneficial benefits to patients, but there must still be greater dissemination and scientific studies, aiming at improving the technique and standardizing the protocols.